Autonomy deficits as vulnerability for anxiety: evidence from two laboratory-based studies. Issue 3 (4th May 2019) - Kunst, L. E.; Maas, J.; Van Assen, M. A. L. M.; Van der Heijden, W.; Bekker, M. H. J.
ABSTRACT: Background: Autonomous individuals are characterized by self-governance; awareness of and capacity to realize one's wishes and needs, while being connected with and sensitive towards others. In line with earlier research showing consistent associations between autonomy-connectedness deficits and anxiety, we tested in two studies whether autonomy deficits predict anxious responses to acute stressors. Methods: In Study 1, participants ( N  = 177) viewed an anxiety-inducing film fragment and reported anxiety before and after viewing the clip. In experimental Study 2, participants ( N  = 100) were randomly allocated to one of two conditions: giving a short presentation to an audience (impromptu speech task) or watching another person's presentation (control condition). Anxiety was measured at baseline, after a preparation period and directly after the presentation. Results: In Study 1, individuals' anxiety in reaction to watching the movie was positively associated with the autonomy-connectedness component sensitivity to others. In Study 2, individuals' anxiety in reaction to preparing the presentation was negatively associated with the autonomy-connectedness component self-awareness. Conclusions: Specific autonomy components may be related to experiencing anxiety in differing situations (i.e., related to others' distress or presenting one's personal views). Collectively these results indicate that autonomy-connectedness deficits may form a vulnerability factor for experiencing anxiety.